Analisis Fiqh Siyasah Terhadap Fenomena Serangan Fajar: Perspektif Hukum Islam Dalam Konteks Keamanan Pemilu - Safaruddin Safaruddin; Tafrihatul Ula (Ma'had Aly Raudhatul Ma'arif, 2024)
General elections (Pemilu) are a critical milestone in the democratic system of a country, determining the selection of leaders and the political direction of the nation. However, the phenomenon of